2020
DOI: 10.3390/cryst10040267
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Non-Covalent Interaction, and Natural Bond Orbital Studies on Bromido-Tricarbonyl Rhenium(I) Complexes Bearing Alkyl-Substituted 1,4-Diazabutadiene (DAB) Ligands

Abstract: The synthesis, characterization, structural and computational studies of Re(I) tricarbonyl bromo complexes bearing alkyl-substituted 1,4-diazabutadiene ligands, [Re(CO)3(1,4-DAB)Br], where 1,4-DAB = N,N-bis(2,4-dimethylbenzene)-1,4-diazabutadiene, 2,4-Me2DAB (1); N,N-bis(2,4-dimethylbenzene)-2,3-dimethyl-1,4-diazabutadiene, 2,4-Me2DABMe (2); N,N-bis(2,4,6-trimethylbenzene)-1,4-diazabutadiene, 2,4,6-Me3DAB (3); and N,N-bis(2,6-diisopropylbenzene)-1,4-diazabutadiene, 2,6-ipr2DAB (4) are reported. The complexes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In addition to the exploration of the [2 + 1] strategy for the design of new Re(I) complexes by using the appropriate ligands, there is an increased interest on the study of intermolecular interactions of Re(I) complexes in the solid state [ 33 35 ] based on diverse types of interactions of rhenium complexes with DNA [ 36 , 37 ]. Similar systematic crystal structure studies [ 38 40 ] have revealed the importance of lone pair π and more specifically the role of carbonyl-carbonyl interactions on the supramolecular assembly of Re complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the exploration of the [2 + 1] strategy for the design of new Re(I) complexes by using the appropriate ligands, there is an increased interest on the study of intermolecular interactions of Re(I) complexes in the solid state [ 33 35 ] based on diverse types of interactions of rhenium complexes with DNA [ 36 , 37 ]. Similar systematic crystal structure studies [ 38 40 ] have revealed the importance of lone pair π and more specifically the role of carbonyl-carbonyl interactions on the supramolecular assembly of Re complexes.…”
Section: Introductionmentioning
confidence: 99%
“…To this effect, the study of metal carbonyls complexes on the basis of participation in a n→π* interaction similar to their organic counterparts and related to their role in catalysis are of considerable interest. Therefore, in a continuation of our interest in intra-and intermolecular n→π* interactions in metal-carbonyl complexes, [27][28][29][30] herein, we report the synthesis, full structural and computational studies of two new Re(CO)3 complexes bearing diimine ligands with a coordinated perrhenate, formed via superoxidation of Re(I), and its potential as supramolecular synthon for assembly through n→π* interactions. Please do not adjust margins Please do not adjust margins the [Re(CO)3(Ph4TAP)] + and [Re(CO)3(Dafone)] + cations to form the neutral di-rhenium mixed oxidation state complexes in good yields (69% for 1 and 70% for 2).…”
mentioning
confidence: 99%